Fault Location Method for Communication Link with Multi-information Fusion Modeling of Smart Substation - Zhiyong PI; Yi ZHU; Xuan LIAO; Zhenxing LI; Hao FANG; Pei WU (Zhongguo dianli)
In order to solve such problems of smart substations as numerous alarm information caused by communication link failure and poor operation efficiency, a fault location method for communication link is proposed with multi-information fusion modeling of smart substation. Firstly, a communication network numbering principle is proposed by traversing the device nodes of SCD. Secondly, by fusing multiple alarm information, the node and link coding rules are formulated, and the node-link mapping relationship and positioning model are established. And then, the adaptive genetic particle swarm algorithm is used to solve the positioning model to achieve accurate positioning of link faults. Finally, taking the secondary network of a 220 kV smart substation as an example, the effectiveness of the proposed method is verified under different link failure scenarios.